Korea : The Korean Pension System at a Crossroads - World Bank (Washington, DC, 2013)
Old age income security in Korea is at a crossroads. The traditional system of family support is giving way to formal retirement savings--most of it mandated by government. Government employees and private school teachers are obliged to participate in special occupational schemes that operate on a pay-as-you-go basis while private sector workers must contribute to the partially funded National Pension Scheme (NPS). Employers must provide retirement allowances, a retirement cum severance payment program whose obligations are largely unfunded. These schemes have evolved over several decades and are not based on clear targets for the level of mandated retirement income or sustainable payroll tax burdens. They currently pay benefits to a minority of older Koreans. This means that over the next few years only social assistance programs will have a significant impact on the incomes of the current elderly poor. This report presents several alternative reform options. These include reforms to some elements of the existing system as well as an integrated or systemic reform option. The proposed reform allows younger workers to opt out of the earnings-related portion of the NPS. The combination of a mandatory private pension scheme--which would replace retirement allowances--and a reduced public pension scheme would result in a reasonable replacement rate target. New entrants would be obliged to join this system while older workers would continue to be covered by the current scheme.